Transcriptome and metabolome analyses of Shatian pomelo (Citrus grandis var. Shatinyu Hort) leaves provide insights into the overexpression of the gibberellin-induced gene CcGASA4 - Wu, Tianli; Liu, Kaidong; Chen, Min; Jiang, Bo; Gong, Qijing; Zhong, Yun (Frontiers in Plant Science, 2022)
The GA-stimulated Arabidopsis (GASA) gene family is highly specific to plants and plays crucial roles in plant growth and development. CcGASA4 is a member of the GASA gene family in citrus, however, its function in citrus is still limited. Using CcGASA4-overexpression transgenic citrus (OEGA) and the control plants (CON), RNA-seq and LC-MS/MS-based untargeted metabolomic analyses were performed to address the role of CcGASA4 in Shatian pomelo. RNA-seq results showed that 3522 genes, including 1578 up-regulated and 1944 down-regulated genes, were found to be significantly different in the CON -vs.- OEGA. According to the GO enrichment analysis results, 178 differentially expressed genes (DEGs) were found to be related to flowers. The results of KEGG enrichment analysis showed that DEGs were enriched in 134 KEGG pathways, including "plant-pathogen interaction", "MAPK signaling pathway-plant", "phenylpropane biosynthesis", "plant hormone signal transduction", "phenylalanine, tyrosine and tryptophan biosynthesis" and "flavonoid and flavonol biosynthesis". Among them, the most significant enrichment pathway was "plant-pathogen interaction", and a total of 203 DEGs were enriched (126 DEGs were up-regulated and 78 DEGs were down-regulated). Metabolome results showed that a total of 644 metabolites were detected in OEGA and CON samples, including 294 diﬀerential accumulated metabolites (DAMs, 83 up-regulated versus 211 down-regulated in OEGA comparison to CON). Metabolic pathway analysis showed that these DAMs mainly involved in metabolic pathways of secondary metabolites, such as phenylpropanoid, phenylalanine, flavone and flavonol biosynthesis. Moreover, 13 flavonoids and isoflavones were identified as DAMs between OEGA and CON. We also discovered 25 OEGA specific accumulated metabolites, and the analysis found 10 metabolites to be associated with disease resistance. These findings indicated that CcGASA4 may play a functional role by activating the expression of MAPK signaling transduction pathway genes and disease resistance genes, by inhibiting the expression of auxin- and ethylene-related genes, and by activating or inhibiting the expression of brassinosteroid biosynthesis and abscisic acid related genes. Furthermore, the results showed that CcGASA4 play a potential role regulation of the composition and abundance of flavonoids and isoflavones, amino acids, purines and phenolic compounds. This study provides new insights into the molecular mechanism of CcGASA4 in citrus.